Improving Children's Fine Motor Skills in Folding Activities with the Demonstration Method of Utilizing Folded Paper Media at RA Miftahul Huda Purwosari Pasuruan - Nisa, Khairun; Khotimah, Husnul (Journal of Indonesian Primary School, 2025)
The fine motor skills of Group A children at RA Miftahul Huda Purwosari Pasuruan have not developed well. This study aims to improve children's fine motor skills through paper folding activities. This study is a Classroom Action Research. The subjects of the study were 18 children in Group A. The object of this study was fine motor skills. Data collection techniques were carried out using observation and documentation. The tool used was an observation instrument sheet. The data analysis technique was carried out descriptively quantitatively. The success indicator set was 75% of 18 children having fine motor skills. This study was conducted in two Cycles. The results showed that the fine motor skills of Group A children in Cycle I were 23.5%, and in Cycle II were 76.4%. The percentage obtained in Cycle II proved that this study had achieved the success indicator, namely that children's fine motor skills had increased by ≥75%. The research steps that can improve fine motor skills are carried out by paper folding activities, using paper media that is quite large in size, and equipped with pictures of learning steps. Based on the research results, it can be concluded that this activity can improve fine motor skills in Group A at RA Miftahul Huda Kertosari Purwosari Pasuruan.